Does financial literacy affect investment decisions? Evidence from Gen Z of vocational program - Rahima, Annisa; Anindya, Khoirina Noor (Jurnal Ekonomi & Studi Pembangunan, 2025)
The rampant fraudulent investment that occurs among college students of various ages in Indonesia has heightened concerns regarding financial literacy, despite their educational backgrounds. This situation prompts synergy between universities and the government to improve financial literacy. This study explores the influence of financial literacy on the investment decisions of generation Z vocational students in Indonesia, who possess more practical skills than theoretical knowledge. Adequate financial literacy is theorized to increase students’ interest in investing, which subsequently influences their investment decisions. This study examines four dimensions of financial literacy: saving literacy, financial behavior literacy, capital market knowledge, and types of investment literacy. This study uses a quantitative approach, with data collected and analyzed using Structural Equation Modeling (SEM) via AMOS. The results show that saving literacy and capital market knowledge have no significant effect on investment interest. Conversely, financial behavior literacy and types of investment literacy positively affect investment interest, which in turn has positive effect on investment decisions. Collaboration is needed between educational institutions and the government to enhance financial literacy, thereby encouraging wiser investment decisions among university students.